2021
DOI: 10.3390/su13052692
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable Economic Growth Support through Credit Transmission Channel and Financial Stability: In the Context of the COVID-19 Pandemic

Abstract: All countries worldwide faced the COVID-19 pandemic and had to take actions to lower the economic shock. Financial authorities play an especially significant role in economics and can help to manage the negative consequences. This article focuses on the European central bank monetary policy and actions taken for COVID-19 risk management. This research aims to identify the significant factors influencing the long-term loans for enterprises’ credit conditions in a forward-looking approach and determine the impac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 50 publications
(34 reference statements)
0
14
0
3
Order By: Relevance
“…Restructuring is necessary for the banking system to avoid future losses (Kloks, 2021;Teresienė et al, 2021). This is inseparable from the strategy pursued by sharia bank managers, including risk mitigation by mapping debtors, who are feasible to be restructured and who are not yet feasible (Ariffin & Kassim, 2014…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Restructuring is necessary for the banking system to avoid future losses (Kloks, 2021;Teresienė et al, 2021). This is inseparable from the strategy pursued by sharia bank managers, including risk mitigation by mapping debtors, who are feasible to be restructured and who are not yet feasible (Ariffin & Kassim, 2014…”
Section: Discussionmentioning
confidence: 99%
“…Government Regulation Number 21 of 2020 to reduce the transmission of COVID-19 has an impact on the performance of business activities, including banks and their partners (Teresienė et al, 2021). The announcement of COVID-19 and government regulations related to this phenomenon caused the development of existing businesses in Indonesia to be limited.…”
Section: Literature Review and Hypothesesmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the U.S. fiscal policy provided some compensation for households and businesses. Even though both monetary and fiscal policy could be viewed as a way to stimulate economic development, (Teresiene et al, 2021) indicate that the monetary policy has limited possibilities to support the economy. On the other hand, the containment policy, including entry restrictions, social distancing mandates and put on lockdown, might damage the economic (Baldwin and Tomiura, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…This slowdown has been recently compounded by the COVID-19 pandemic. Teresiene et al (2021) found that "the spread of the COVID-19 pandemic has a statistically significant negative effect on banking sector credit risk, financial distress, banking sector profitability, and solvency". In addition, "while the overall financial distress decreased and banking sector liquidity increased, the profitability and solvency decreased".…”
Section: Introductionmentioning
confidence: 99%